E-Cadherin Is Important in the In Vitro Postnatal Development and Function of Pig Islets - Kieran Purich; Josue Rodriguez Silva; Wenlong Huang; James Wickware; Thomas Williams; Adnan Black; Jeongbeen Kim; David Fernandez Chapa; Sudha Bhavanam; David Bigam; Daniel Schiller; Gina R. Rayat (Biomedicines)
Background: Pig islets have the potential to address the limited supply of human islets available for transplantation. However, the knowledge of the biology of pig islets is currently limited. Thus, this study evaluated the molecules involved in cell-to-cell adhesion and insulin secretion pathways during the in vitro development of neonatal pig islets to understand the tissue we hope to use as a possible solution to the shortage of human islets for transplantation. Methods: Through RT-qPCR, immunoassays, and assessments of islet function, we explored the expression of E-cadherin and its correlation with the molecules involved in the insulin secretion pathway including GTPase, RAC1, and the membrane fusion protein SNAP25 during neonatal pig islet development. Results: Despite no significant difference observed in gross morphology and viability, as well as variable expression of RAC1, insulin, and SNAP25 in islets from 1-, 3-, and 7-day-old neonatal pigs, there was an apparent trend towards improved function in islets obtained from 3- and 7-day-old pigs compared with 1-day-old pigs. In the presence of 30 mM KCl, the amount of insulin secreted by islets from 3- and 7-day-old pigs but not from 1-day-old pigs was increased. Disruption of E-cadherin interactions with monoclonal antibodies resulted in decreased insulin secretion capacity of islets from 3-day old pigs. Conclusions: Our results show that blocking E-cadherin interactions with monoclonal antibodies resulted in disrupted peri-islet capsule and impaired islet insulin secretion under high glucose conditions. Thus, E-cadherin is important in the in vitro postnatal development and function of pig islets.